Widespread misperception about a major East Asian biogeographic boundary exposed through bibliographic survey and biogeographic meta‐analysis. (27th June 2021) - Komaki, Shohei
Abstract: Aim: The Watase line, a major biogeographic boundary between Palearctic and Oriental realms in East Asia, is generally drawn between Akuseki and Kodakara Islands of the Northern Ryukyu archipelago, Japan. However, no evidence can be found to support the positioning of the boundary between these two tiny volcanic islands. This study aimed to confirm whether and where the biogeographical boundary should be drawn. Location: East Asia. Taxon: Land snail, ant, dragonfly, butterfly, amphibian, reptile, bird and plant. Methods: A bibliographic survey was carried out to revisit an original definition of the Watase line and its usage. Biogeographic and meta‐analyses were also performed using a Simpson dissimilarity index calculated from published distribution data to test whether and where any biogeographic boundary exists. To ensure the validity of the study design, similar surveys and analyses were conducted in another region of Southern Ryukyu, where a reliable biogeographic boundary has been proposed as a positive control. Results: The bibliographic survey showed that the Watase line had been described without specifying the precise position. No revised definition has been proposed for the boundary to date. Biogeographic analyses do not support the existence of a boundary between Akuseki and Kodakara Islands. Meanwhile, the presence of a boundary in Southern Ryukyu was endorsed by both the bibliographic survey and biogeographic analyses, supporting the validity of this study's design. Main conclusions: This study revealed that the major biogeographic boundary is widely used with deviations from the original definition. Presumably, ideas based on inappropriate evidence, such as the distribution of a symbolic species and unpublished data, have been referred to without being questioned and led to the current widespread misunderstanding. Misunderstandings like these could occur at any biogeographic boundaries around the world, and thus, systematic reviews of all boundaries are needed for an appropriate understanding of biodiversity.